Standardization of Immunobiological Assay for Determines Identity of Junin virus Vaccine, Candid#1 - Chale, Julieta; Maiza, Andrea S.; Gamboa, Graciela S.; Riera, Laura M. (2019)
The quality control tests of the Candid#1 vaccine required for internal release needs the use of rabbit immune serum (RIS). It is a biological reagent produced in INEVH and it must be qualied to ensure its proper use. The aim of this study was to estimate the expanded uncertainty (U) through validation studies of identity test in which the titles of IRS are determined, and thus establish its specication for use in control tests where the title of it is critical. Validation studies made possible calculate the U established by statistical analysis of the values obtained experimentally in intermediate precision, resulting=0.30. Determination of the U of the methodology established that 500 is the minimum qualication that must have an IRS to be used in quality control testing of the vaccine Candid# 1.